Food as medicine: how eating halal and tayyib contributes to a balanced lifestyle - Elgharbawy, Amal A.M.; Azmi, Nor Azrini Nadiha (International Institute for Halal Research and Training (INHART), 2022)
Food is not just to satisfy one’s desires, but it is a way of maintaining one’s health and constantly striving to worship Allah. While the concept of eating as medicine is not new, Islam had already given guidelines on eating food through the Qur’an and Sunnah from the Prophet and the companions. In Islam, the concept of eating is based on halal and toyyib, which describes eating permissible and wholesome food according to Islamic principles. However, Muslims nowadays ignore this concept, which is taking tolls on their daily lives, making them mentally and physically unhealthy. Islam emphasises food intake because of the significant impact it may have on physical and mental well-being and the soul of an individual. The types of diet in line with Islamic teaching are also described from the practice of the Prophets. The information is collected using Scopus and Google Scholar databases in addition to the primary two sources: the Qur’an and Sunnah. The reported evidence from Qur’an and Sunnah were from trusted sources, and references are provided. The contribution of this article is to set guidelines to achieve a balanced lifestyle by consuming halal and toyyib, deriving that from prophetic practices.